Topical Glucocorticoid Use and the Risk of Posttransplant Diabetes - Simon Bøtker; Henrik Birn; Lara Aygen Øzbay (Case Reports in Endocrinology)
Systemically administered glucocorticoids constitute an essential part of the immunosuppressive regimen for transplant recipients, yet their known risks of causing hyperglycemia or posttransplant diabetes require close monitoring and minimisation of use, when possible, to prevent detrimental effects on patient morbidity and graft survival. Topical glucocorticoids, on the other hand, are rarely considered to affect glucose metabolism and therefore seldomly monitored, despite their wide and in some cases, long-term use. We report a case of a renal transplant recipient presenting with acute hyperosmolar hyperglycemia after treatment with topical glucocorticoids and present a mini review of the literature.